2018
DOI: 10.3390/ma11101986
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of a Docosahexaenoic Acid (DHA)-Rich Lipid Fraction from Thraustochytrium sp. Using Ionic Liquids

Abstract: Polyunsaturated fatty acids (PUFAs) play a significant role in the modulation and prevention of various diseases, and hence are attracting increasing attention from the biotech industry. Thraustochytrids are marine heterokonts that exhibit robust growth rates, high PUFA content, and more specifically, a large percentage of omega-3 fatty acids like docosahexaenoic acid (DHA). Recently, ionic liquids (ILs) have been shown to improve the efficiency of organic solvent extraction of oils from wet oleaginous yeast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…According to the results, C22:6n-3 (DHA) was the major component found in all extracts, indicating that T18 was a good source of DHA. Furthermore, the study showed that the extraction was not of high quality and the ILs used were unable to extract the DHA with high selectivity; instead they extracted the total lipids available without oxidizing the unsaturated bonds [76]. This is in agreement with the COSMO-RS results, which showed that propanoate is indeed an excellent option for extraction when combined with ethyl cations.…”
Section: The Effect Of Different Anion Types On Capacity Value Of Ilssupporting
confidence: 76%
See 1 more Smart Citation
“…According to the results, C22:6n-3 (DHA) was the major component found in all extracts, indicating that T18 was a good source of DHA. Furthermore, the study showed that the extraction was not of high quality and the ILs used were unable to extract the DHA with high selectivity; instead they extracted the total lipids available without oxidizing the unsaturated bonds [76]. This is in agreement with the COSMO-RS results, which showed that propanoate is indeed an excellent option for extraction when combined with ethyl cations.…”
Section: The Effect Of Different Anion Types On Capacity Value Of Ilssupporting
confidence: 76%
“…In a previous study, two ILs (imidazolium 1-ethyl-3-methylimidazolium ethyl sulfate [EMIM][EtSO 4 ] and phosphonium (tetrabutyl phosphonium propanoate [P4444][Prop])) were used as extracting solvents to perform PUFA extraction from Thraustochytriumsp . (T18) [ 76 ]. According to the results, C22:6n-3 (DHA) was the major component found in all extracts, indicating that T18 was a good source of DHA.…”
Section: Resultsmentioning
confidence: 99%
“…The study on the extraction of DHA from Thraustochytrium sp. biomass reported 1-ethyl-3-methylimidazolium ethylsulfate and tetrabutylphosphonium propionate, with the use of IL: methanol at 1:10 and 1:4 ratio, respectively, achieved lipid extraction yield of 91% [106].…”
Section: Lipidsmentioning
confidence: 99%
“…In this context, Cheong et al suggested the correlation of n-3 PUFA extraction and structure of ILs (aromatic/delocalized cation) for the effective extraction of PUFA [46]. The short alkyl chain was used in a recent study [49]. Two types of ILs were used in the extraction of PUFA-containing lipids from Thraustochytrium sp.…”
Section: Capacity Values Of Ils Toward the Ala Moleculesmentioning
confidence: 99%